A supercapacitor

By using a cyclic electrolyte salt and acetonitrile solvent in a supercapacitor, combined with a potassium element active material layer, the interfacial compatibility of the electrode plates was optimized, solving the problems of low impedance and long lifespan in supercapacitors, and achieving higher electrochemical stability and ion transport efficiency.

CN123033901APending Publication Date: 2026-11-03SHENZHEN CAPCHEM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611530360.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-30
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing supercapacitors struggle to balance low impedance and long lifespan. Traditional organic electrolyte systems suffer from severe solute decomposition under high voltage, leading to rapid capacity decay and insufficient pore utilization.

Method used

A compound with a cyclic structure is used as the electrolyte salt and acetonitrile as the organic solvent. Combined with an active material layer containing potassium, a synergistic structure is formed by controlling the potassium content and electrolyte composition, thereby optimizing the ion transport channel and the compatibility of the electrode plate interface.

Benefits of technology

It significantly reduces the overall impedance of supercapacitors, improves cycle life and wide temperature range performance under high voltage, and solves the technical bottleneck of low impedance and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123033901A_ABST
    Figure CN123033901A_ABST
Patent Text Reader

Abstract

In order to overcome the problem that the existing super capacitor is difficult to balance low impedance and cycle life, the application provides a super capacitor, which comprises a diaphragm, an electrolyte and two electrode plates, the diaphragm is located between the two electrode plates, the electrode plate comprises a current collector and an active material layer arranged on at least one side surface of the current collector, the active material layer comprises carbon material and K element, the mass content of K element in the active material layer is u ppm, the electrolyte comprises an organic solvent and an electrolyte salt, the organic solvent comprises acetonitrile, the electrolyte salt comprises a compound shown in structural formula 1, the content of the compound shown in the structural formula 1 is a%, and the content of the acetonitrile is b% based on the total mass of the electrolyte; the super capacitor satisfies the following conditions: 0.1<=u*b / (100a)<=28, and 13<=a<=49, 51<=b<=87, and 2<=u<=500.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of energy storage electronic components technology, and specifically relates to a supercapacitor. Background Technology

[0002] Among numerous energy storage devices, electrochemical double-layer capacitors (EDLCs) store energy by electrostatically depositing an electrolyte. Their energy storage mechanism involves no chemical reaction and is highly reversible. They can be viewed as two unrelated porous plates separated by an electrolyte when an external voltage is applied to the two plates. The potential applied to the positive plate attracts negative ions, while the potential of the negative plate attracts positive ions. This effectively creates two charge reservoirs, one separated at the positive plate and the other at the negative plate. Based on its energy storage mechanism, it is easy to see that, due to its unique physical adsorption / desorption charge storage mechanism, compared with traditional secondary batteries (such as lithium-ion batteries) involving redox reactions, it has advantages such as high power density, long cycle life, high safety factor, wide operating temperature range, and fast charge / discharge, making it widely used in key areas such as wind power pitch control systems, vehicle energy recovery systems, grid frequency regulation, and uninterruptible power supplies.

[0003] Currently, the organic electrolyte system commonly used in commercial supercapacitors is tetraethylammonium tetrafluoroborate (TEABF4) or 1,1-spirobispyrrolidone tetrafluoroborate (SBPBF4) dissolved in acetonitrile (ACN) or propylene carbonate (PC). Among them, acetonitrile (ACN) has low viscosity and high dielectric constant, which can endow the electrolyte with high ionic conductivity and excellent low-temperature performance, and therefore it is widely used in high-performance supercapacitors.

[0004] However, with the development of application requirements, the need for lower impedance (ESR) and longer lifespan has emerged. Although the TEABF4 / ACN and SPBF4 / ACN systems have been commercially applied, their large cation radii result in insufficient utilization of activated carbon pores, leading to high adsorption and desorption resistance and thus high impedance. At operating voltages of 3.0V and higher, traditional quaternary ammonium salt electrolyte systems also suffer from severe solute decomposition, resulting in rapid capacity decay and failing to meet the long lifespan requirement. Currently, organic electrolyte systems for supercapacitors can use one or more combinations of acetonitrile (ACN), propylene carbonate (PC), sulfolane (SL), γ-butyrolactone (GBL), or other solvents. However, these combined solvents have high viscosity and low conductivity, failing to meet the performance requirements for low impedance.

[0005] Therefore, there is an urgent need to develop a supercapacitor electrolyte system that combines high ionic conductivity, low impedance, excellent long lifespan, and good electrode plate interface compatibility. Summary of the Invention

[0006] To address the problem that existing supercapacitors struggle to balance low impedance and cycle life, this invention provides a supercapacitor.

[0007] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: This invention provides a supercapacitor, comprising a separator, an electrolyte, and two electrode plates. The separator is located between the two electrode plates. Each electrode plate includes a current collector and an active material layer disposed on at least one surface of the current collector. The active material layer includes carbon material and potassium (K) element. The mass content of K element in the active material layer is μ ppm based on the total mass of the active material layer. The electrolyte comprises an organic solvent and an electrolyte salt, wherein the organic solvent comprises acetonitrile, and the electrolyte salt comprises a compound shown in structural formula 1. Structural Formula 1 Among them, A - R1 and R2 are anions, each independently selected from C1 to C3 alkyl groups, and n is 0 or 1; Based on the total mass of the electrolyte, the content of the compound represented by structural formula 1 is a%, and the content of acetonitrile is b%. The supercapacitor satisfies the following conditions: 0.1≤u*b / (100a)≤28, and 13≤a≤49, 51≤b≤87, 2≤u≤500.

[0008] Optionally, the supercapacitor satisfies at least one of the following conditions: (1)0.2≤u*b / (100a)≤12; (2) 17.5 ≤ a ≤ 39.5; (3) 60.5 ≤ b ≤ 82.5; (4) 10≤u≤300.

[0009] Optionally, the supercapacitor satisfies: 98≤a+b≤100.

[0010] Optionally, the carbon material includes one or more of activated carbon, nano-carbon, graphene, lignin carbon, mesoporous carbon, carbon nanotubes, or porous carbon fibers.

[0011] Optionally, the compaction density of the active material layer is 0.5~1.0 g / cm³. 3 .

[0012] Optionally, the electrolyte has a conductivity of 30–65 mS / cm at 25°C.

[0013] Optionally, based on the total mass of the electrolyte, the content a% of the compound represented by structural formula 1 satisfies 17.5 ≤ a ≤ 39.5%.

[0014] Optionally, the acetonitrile content b% based on the total mass of the electrolyte satisfies 60.5 ≤ b ≤ 82.5.

[0015] Optionally, the mass content u ppm of K element in the active material layer satisfies 10 ≤ u ≤ 300.

[0016] Optionally, the anion A of the compound represented by structural formula 1 - Including one or more of tetrafluoroborate, hexafluorophosphate, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, bis(trifluoromethylsulfonyl)methyl, and perfluoroalkylsulfonate; and / or, The cation of the compound shown in structural formula 1 includes one or more of N,N-dimethylpyrrolidineonium, N,N-diethylpyrrolidineonium, N,N-dipropylpyrrolidineonium, N-methyl-N-ethylpyrrolidineonium, N-methyl-N-propylpyrrolidineonium, N-ethyl-N-propylpyrrolidineonium, N,N-dimethylpiperidineonium, N,N-diethylpiperidineonium, N,N-dipropylpiperidineonium, N-methyl-N-ethylpiperidineonium, N-methyl-N-propylpiperidineonium, and N-ethyl-N-propylpiperidineonium.

[0017] Optionally, the anion A of the compound represented by structural formula 1 - It is tetrafluoroborate.

[0018] Optionally, the organic solvent is acetonitrile, and the compound represented by structural formula 1 is N,N-dimethylpyrrolidone tetrafluoroborate.

[0019] Optionally, the charging cutoff voltage of the supercapacitor is 2.7~3.2V.

[0020] Optionally, the supercapacitor operates in a temperature range of -40℃ to 65℃.

[0021] The supercapacitor provided by this invention uses a compound with a cyclic structure as shown in Formula 1 as the electrolyte salt. This compound has a smaller cation radius, higher structural rigidity, and significantly better oxidation stability and resistance to voltage decomposition than the traditional TEABF4 and SPBF4 systems. This effectively reduces capacity decay caused by solute decomposition under high voltage, achieving a longer cycle life. Simultaneously, the smaller ionic radius allows it to more fully penetrate the microporous structure of activated carbon, reducing ion adsorption / desorption resistance and thus significantly lowering the equivalent series resistance (ESR) of the supercapacitor. Acetonitrile, as an organic solvent, possesses low viscosity, high dielectric constant, and strong coordination ability. It exhibits excellent solubility and dissociation for the aforementioned quaternary ammonium salt, with a solubility reaching 67%, ensuring rapid ion transport in the electrolyte. Furthermore, acetonitrile itself has advantages such as high stability, resistance to oxidation, and low decomposition, providing fundamental physical properties for the long lifespan of the supercapacitor.

[0022] Specifically, the introduction of potassium (K) into the active material layer of the electrode plate improves the electronic conductivity and ion transport performance of the electrode plate material, reducing the bulk impedance of the electrode plate. Furthermore, it allows the K element to firmly adhere to the surface of the active material layer. When the supercapacitor is injected with the compound / acetonitrile electrolyte of the aforementioned structural formula 1, the pre-embedded K element pre-constructs a low-barrier ion transport channel for the subsequently introduced cations of the compound of structural formula 1, effectively alleviating the pore adsorption / desorption resistance faced by the cations and further reducing the electrode plate-electrolyte interface impedance of the supercapacitor. This invention combines the compound / acetonitrile electrolyte of the specific structural formula 1 with a K-containing electrode plate material, rationally controlling the K element content to form a synergistic structure of K doping in the electrode plate and a specific electrolyte system.

[0023] Based on the synergistic effect between the content of compound a% and acetonitrile b% in the electrolyte as shown in Structural Formula 1 and the content of K element u ppm in the active material layer, the inventors discovered through extensive research that when the three conditions are met (0.1≤u*b / (100a)≤28, 13≤a≤49, 51≤b≤87, 2≤u≤500), the optimal coupling between the K element pre-channel effect and the rapid transport of cations of the compound shown in Structural Formula 1 can be achieved. This significantly reduces the overall impedance of the supercapacitor and greatly improves the cycle life and wide temperature range performance of the supercapacitor under high voltage, thus solving the technical bottleneck of existing supercapacitors that are difficult to balance low impedance and long life. Detailed Implementation

[0024] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0025] In the description of this invention, the term "C1-C3 alkyl" includes straight-chain alkyl and branched-chain alkyl.

[0026] This invention provides a supercapacitor, including a separator, an electrolyte, and two electrode plates. The separator is located between the two electrode plates. Each electrode plate includes a current collector and an active material layer disposed on at least one surface of the current collector. The active material layer includes carbon material and potassium (K) element. The mass content of K element in the active material layer is μ ppm based on the total mass of the active material layer. The electrolyte comprises an organic solvent and an electrolyte salt, wherein the organic solvent comprises acetonitrile, and the electrolyte salt comprises a compound shown in structural formula 1. Structural Formula 1 Among them, A - R1 and R2 are anions, each independently selected from C1 to C3 alkyl groups, and n is 0 or 1; Based on the total mass of the electrolyte, the content of the compound represented by structural formula 1 is a%, and the content of acetonitrile is b%. The supercapacitor satisfies the following conditions: 0.1≤u*b / (100a)≤28, and 13≤a≤49, 51≤b≤87, 2≤u≤500.

[0027] The supercapacitor uses a compound with a cyclic structure, as shown in Formula 1, as the electrolyte salt. This compound has a smaller cation radius, higher structural rigidity, and significantly better oxidation stability and resistance to voltage decomposition than the traditional TEABF4 and SPBF4 systems. This effectively reduces capacity decay caused by solute decomposition under high voltage, resulting in a longer cycle life. Simultaneously, the smaller ionic radius allows it to more fully penetrate the microporous structure of carbon materials, reducing ion adsorption / desorption resistance and thus significantly lowering the equivalent series resistance (ESR) of the supercapacitor. Acetonitrile, as an organic solvent, possesses low viscosity, high dielectric constant, and strong coordination ability. It exhibits excellent solubility and dissociation of the aforementioned quaternary ammonium salt (solubility reaches 67% at 25°C), ensuring rapid ion transport in the electrolyte. Furthermore, it possesses high stability, is not easily oxidized, and is not easily decomposed, providing fundamental physical properties for the long lifespan of the supercapacitor.

[0028] Specifically, the introduction of potassium (K) into the active material layer of the electrode plate improves the electronic conductivity and ion transport performance of the electrode plate material, reducing the bulk impedance of the electrode plate. Furthermore, it allows the K element to firmly adhere to the surface of the active material layer. When the supercapacitor is injected with the compound / acetonitrile electrolyte of Structural Formula 1, the pre-embedded K element pre-constructs a low-barrier ion transport channel for the subsequently introduced cations of the compound of Structural Formula 1, effectively alleviating the pore adsorption / desorption resistance faced by the cations and further reducing the electrode plate-electrolyte interface impedance of the supercapacitor. This invention combines the compound / acetonitrile electrolyte of the specific Structural Formula 1 with an electrode plate material containing K element, rationally controlling the K element content to form a synergistic structure between the K element in the electrode plate and the specific electrolyte system.

[0029] Based on the synergistic effect between the content of compound a% and acetonitrile b% in the electrolyte as shown in Structural Formula 1 and the content of K element u ppm in the active material layer, the inventors discovered through extensive research that when the three conditions are met (0.1≤u*b / (100a)≤28, 13≤a≤49, 51≤b≤87, 2≤u≤500), the optimal coupling between the K element pre-channel effect and the rapid transport of cations of the compound shown in Structural Formula 1 can be achieved. This significantly reduces the overall impedance of the supercapacitor and greatly improves the cycle life and wide temperature range performance of the supercapacitor under high voltage, thus solving the technical bottleneck of existing supercapacitors that are difficult to balance low impedance and long life.

[0030] In a preferred embodiment, the supercapacitor satisfies the following conditions: 0.2≤u*b / (100a)≤12.

[0031] This ratio reflects the matching relationship between the density of K element sites on the electrode plate surface and the cation supply in the electrolyte. When the ratio further meets the above conditions, it can ensure that the number of ion transport channels formed by K elements is optimally balanced with the number of migrateable cations in the electrolyte. This avoids the problems of insufficient ion transport channels formed by K elements, large cation adsorption / desorption resistance, and increased impedance caused by an excessively small ratio, while also preventing the problems of excessive K elements occupying active sites of activated carbon without participating in transport, resulting in decreased double-layer capacitance and deteriorated lifetime caused by an excessively large ratio. This achieves a synergistic improvement in low impedance and long lifetime.

[0032] In a specific embodiment, based on the total mass of the electrolyte, the content a% of the compound represented by structural formula 1 can be 13%, 14.5%, 16.5%, 17.5%, 20%, 21.8%, 25%, 30.5%, 35%, 39.5%, 41%, 43%, 45%, 48%, 49%, or any two of these ranges.

[0033] In a preferred embodiment, the content a% of the compound represented by structural formula 1 satisfies 17.5 ≤ a ≤ 39.5.

[0034] In a preferred embodiment, the content a% of the compound represented by structural formula 1 satisfies 21.8 ≤ a ≤ 30.5.

[0035] The content of electrolyte salts directly affects the ion concentration and viscosity of the electrolyte. When the content of the compound shown in structural formula 1 is within the above range, the electrolyte can maintain a high ionic conductivity while avoiding the problems of increased electrolyte viscosity and increased ion migration resistance caused by excessive salt content.

[0036] In a specific embodiment, the acetonitrile content b% can be 51%, 53%, 56%, 58%, 60.5%, 64%, 69.5%, 71%, 75%, 78%, 82.5%, 83%, 85%, 87%, or any range between two of these.

[0037] In a preferred embodiment, the acetonitrile content b% satisfies 60.5 ≤ b ≤ 82.5.

[0038] Acetonitrile, as the main solvent in the electrolyte, determines the electrolyte's viscosity and its solubility for electrolyte salts. Acetonitrile possesses characteristics of low viscosity, high dielectric constant, and strong coordination ability, exhibiting excellent solubility and dissociation for the compound shown in structural formula 1. When the acetonitrile content is within the aforementioned range, it can fully dissolve the electrolyte salts, ensuring the electrolyte has low viscosity and high ion migration rate, thus providing a foundation for the low impedance performance of supercapacitors.

[0039] In a preferred embodiment, the content of the compound shown in structural formula 1 (a%) and the content of the acetonitrile (b%) satisfy: 98 ≤ a + b ≤ 100. The electrolyte is mainly composed of the compound shown in structural formula 1 and acetonitrile, without the addition of other solvents, electrolyte salts, or additives. This avoids the adverse effects of increased impedance or shortened lifespan caused by combined solvents or electrolyte salts. While adding additives can improve the decomposition and consumption rate of solvents and electrolyte salts to some extent, the improvement effect is limited, and the preferential decomposition of the additives themselves may be detrimental, leading to gas production and blockage of carbon material pores, resulting in increased capacitor impedance and reduced lifespan. Therefore, the electrolyte of this application does not require the addition of additional additives.

[0040] In a preferred embodiment, the electrolyte does not contain carbonate solvents. Carbonate solvents have a higher boiling point than acetonitrile and can withstand higher operating temperatures, but they have a high viscosity and their solubility for electrolyte salts is far less than that of acetonitrile, resulting in a higher impedance than the pure acetonitrile system.

[0041] In some embodiments, the K element in the active material layer may be introduced into the carbon material by doping during the preparation of the carbon material, or by adding potassium salts such as potassium tetrafluoroborate (KBF4) and potassium acetate (CH3COOK) during the slurry preparation of the electrode plate.

[0042] In a specific embodiment, the mass content u ppm of K element in the active material layer can be 2ppm, 10ppm, 30ppm, 50ppm, 80ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm or any two of these ranges.

[0043] In a preferred embodiment, the mass content u ppm of K element in the active material layer satisfies 10 ≤ u ≤ 300.

[0044] The potassium (K) element in the active material layer is used to construct a rapid transport channel between the carbon material of the electrode plate and the ions of the compound shown in Structural Formula 1. If the K content is too low, sufficient low-barrier ion transport channels cannot be formed, and the effect of reducing interface impedance is not significant. If the K content is too high, it will occupy the pore structure of the activated carbon and may even cause a reduction reaction, resulting in the electrolyte cations being unable to effectively utilize the pores of the carbon material, causing capacity decay and performance degradation. When the K content is within the above range, it can fully play its role in improving the conductivity of the electrode plate and constructing ion pre-channels, while avoiding adverse effects on the pore structure of the carbon material.

[0045] In some embodiments, the anion A of the compound represented by structural formula 1 - It includes one or more of tetrafluoroborate, hexafluorophosphate, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, bis(trifluoromethylsulfonyl)methyl and perfluoroalkylsulfonate.

[0046] In some embodiments, the cation of the compound represented by structural formula 1 includes one or more of N,N-dimethylpyrrolidineonium, N,N-diethylpyrrolidineonium, N,N-dipropylpyrrolidineonium, N-methyl-N-ethylpyrrolidineonium, N-methyl-N-propylpyrrolidineonium, N-ethyl-N-propylpyrrolidineonium, N,N-dimethylpiperidineonium, N,N-diethylpiperidineonium, N,N-dipropylpiperidineonium, N-methyl-N-ethylpiperidineonium, N-methyl-N-propylpiperidineonium, and N-ethyl-N-propylpiperidineonium.

[0047] In a preferred embodiment, the anion A of the compound represented by structural formula 1 -It is tetrafluoroborate. Compared with anions such as hexafluorophosphate, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, bis(trifluoromethylsulfonyl)methyl, and perfluoroalkylsulfonate, tetrafluoroborate has excellent electrochemical stability and a smaller ionic radius. It is difficult to decompose under high temperature and high pressure conditions, and it also has a higher utilization rate of the pores of carbon materials.

[0048] In a preferred embodiment, the organic solvent is acetonitrile, and the compound represented by structural formula 1 is N,N-dimethylpyrrolidone tetrafluoroborate.

[0049] In some embodiments, the electrolyte salt further includes an auxiliary salt, which includes tetraethylammonium tetrafluoroborate (TEABF4), tetramethylammonium tetrafluoroborate (TMABF4), trimethylethylammonium tetrafluoroborate (TMEABF4), triethylmethylammonium tetrafluoroborate (TEMABF4), trimethylpropylammonium tetrafluoroborate (TMPABF4), tetraethylammonium hexafluorophosphate (TEAPF6), trimethylethylammonium hexafluorophosphate (TMEAPF6), bis(fluorosulfonyl)imide tetraethylammonium (TEAFSI), bis(trifluoromethylsulfonyl)imide tetraethylammonium (TEATFSI), 1-ethyl-3-methylimidazolium tetrafluoroborate (TEAFSI). The following are one or more of the following: EMIMBF4, 1-butyl-3-methylimidazolium tetrafluoroborate (BMIMBF4), 1,3-dimethylimidazolium tetrafluoroborate (DMIMBF4), 1-propyl-3-methylimidazolium tetrafluoroborate (PMIMBF4), 1-ethyl-3-methylimidazolium hexafluorophosphate (EMIMPF6), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMIMFSI), 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI), tetraphenylphosphonium tetrafluoroborate, tetrabutylphosphonium tetrafluoroborate, tetramethylguanidine tetrafluoroborate, and tetraethylammonium perfluorobutylsulfonate.

[0050] In some embodiments, the content of the auxiliary salt is 0.1-20% based on the total mass of the electrolyte.

[0051] In some embodiments, the organic solvent further includes an auxiliary solvent, which includes propionitrile (PN), butyronitrile (BN), isobutyronitrile, valeronitrile, hexanonitrile, benzonitrile, 3-methoxypropionitrile (MPN), butadionitrile (SN), glutaronitrile, adiponitrile, propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), dipropyl carbonate (DPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoroethylene carbonate (TFEC), fluoromethyl ethylene carbonate (FMC), and sulfolane. (SL), methylcyclobutane, dimethyl sulfone (DMSO2), diethyl sulfone, methyl ethyl sulfone, γ-butyrolactone (GBL), γ-valerolactone (GVL), δ-valerolactone, α-methyl-γ-butyrolactone, 1,3-dioxolane (DOL), 1,4-dioxane (DOX), dimethoxymethane (DMM), diethoxymethane (DEM), ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether, diethylene glycol dimethyl ether (DG), triethylene glycol dimethyl ether (TG), tetraethylene glycol dimethyl ether (TEGDME), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF) or one or more of these.

[0052] In some embodiments, the content of the auxiliary solvent is 0.1-30% based on the total mass of the electrolyte.

[0053] In some embodiments, the active material layer further includes a conductive agent and a binder.

[0054] In some embodiments, the carbon material includes one or more of activated carbon, nano-carbon, graphene, lignin carbon, mesoporous carbon, carbon nanotubes, or porous carbon fibers; the conductive agent includes one or more of acetylene black, carbon black, Ketjen black, carbon fibers, carbon nanotubes, or graphene; and the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, carboxylated styrene-butadiene latex, sodium alginate, or polyacrylic acid.

[0055] In some preferred embodiments, the carbon material is selected from activated carbon. Compared with other carbon materials, activated carbon has high electrical conductivity, high specific surface area, high tap density, and a reasonable pore size distribution, which can accelerate electron transport, increase the contact between the electrode plate material and the electrolyte, accelerate the transport of electrolyte ions, and stably realize the rapid adsorption and desorption of electrolyte anions and cations, which is beneficial for supercapacitors to store more charge.

[0056] In some embodiments, the current collector includes one or more of aluminum foil, carbon-coated aluminum foil, copper foil, porous copper foil, carbon cloth, or graphene film.

[0057] In some embodiments, the diaphragm includes one or more of polyethylene diaphragm, polypropylene diaphragm, polyethylene / polypropylene composite diaphragm, biomass cellulose diaphragm, glass fiber diaphragm, and fiber cloth diaphragm.

[0058] In some embodiments, the compaction density of the active material layer is 0.5~1.0 g / cm³. 3 .

[0059] In a specific embodiment, the compaction density of the active material layer can be 0.5 g / cm³. 3 0.55g / cm 3 0.6g / cm 3 0.65g / cm 3 0.7g / cm 3 0.75g / cm 3 0.8g / cm 3 0.85g / cm 3 0.9g / cm 3 0.95g / cm 3 1.0g / cm 3 Or the range between any two of them.

[0060] The compaction density of the active material layer has a significant impact on the diffusion efficiency of electrolyte salts within the active material layer, and also affects the exposure of potassium (K) sites in the pores of the active material layer. If the compaction density is too low, the electrode plate structure becomes loose and unstable, which is detrimental to the lifespan of the supercapacitor. If the compaction density is too high, the distance between raw material particles decreases, resulting in tighter contact, but the diffusion efficiency of the electrolyte in the active material layer decreases, and the ion transport channels formed by K elements are correspondingly reduced, which is not conducive to the rapid movement of a large number of ions, leading to increased impedance. When the compaction density is within the above-mentioned range, the mechanical strength of the electrode plate, electrolyte diffusion, and ion transport performance can be balanced, achieving a balance between low impedance and long lifespan.

[0061] In some embodiments, the electrolyte has a conductivity of 30–65 mS / cm at 25°C.

[0062] The conductivity of the electrolyte can be measured using a conductivity meter.

[0063] The conductivity of the electrolyte is mainly affected by the combined influence of ion concentration and solvent polarity. The conductivity of the electrolyte can be controlled by adjusting the ratio of different electrolyte salts and the composition of organic solvents in the electrolyte.

[0064] In a specific embodiment, the conductivity of the electrolyte at 25°C can be 30 mS / cm, 40 mS / cm, 46.1 mS / cm, 52.4 mS / cm, 59.2 mS / cm, 60 mS / cm, 65 mS / cm, or any two of these ranges.

[0065] In a preferred embodiment, the electrolyte has a conductivity of 40–60 mS / cm at 25°C.

[0066] High ionic conductivity means lower ion migration resistance in the bulk electrolyte, enabling a faster response to ion transport demands during charge and discharge. This is essential for rapid ion migration within the membrane layer and electrode plate pores, and together with the interface pre-activation effect of K element pre-embedded in the electrode plate, it forms a dual resistance reduction mechanism. If the conductivity is too low, the requirement for low impedance cannot be met; conversely, excessively high conductivity implies an excessive electrolyte salt content, leading to increased electrolyte viscosity. When applied in supercapacitors and combined with a K-doped activated carbon active material layer, this also hinders overall impedance reduction.

[0067] In some embodiments, the charging cutoff voltage of the supercapacitor is 2.7~3.2V.

[0068] In specific implementation, the charging cutoff voltage of the supercapacitor can be 2.7V, 2.75V, 2.8V, 2.85V, 2.9V, 2.95V, 3.0V, 3.05V, 3.1V, 3.15V, 3.2V, or any two of these ranges.

[0069] Within the aforementioned voltage range, the electrolyte system of this invention exhibits excellent electrochemical stability, effectively suppressing solute decomposition and side reactions, thus ensuring a long cycle life for the supercapacitor.

[0070] In a preferred embodiment, the supercapacitor operates in a temperature range of -40°C to 65°C.

[0071] The supercapacitor system of this invention has high ionic conductivity and good stability over a wide temperature range, ensuring that the supercapacitor still has low impedance and high capacitance at low temperatures and long cycle life at high temperatures.

[0072] The present invention will be further illustrated by the following examples.

[0073] Table 1 Note: DMPBF4 is N,N-dimethylpyrrolidone tetrafluoroborate; TEABF4 is tetraethylammonium tetrafluoroborate; SBPBF4 is 1,1-spirobispyrrolidone tetrafluoroborate; PC is propylene carbonate; SL is sulfolane; EC is ethylene carbonate.

[0074] Example 1 The supercapacitor in this embodiment is fabricated as follows: A supercapacitor model was assembled in a glove box: the cell includes two electrode plates and a fiber cloth separator inserted between them. The electrode plates include aluminum foil and active material layers disposed on both sides of the aluminum foil (using activated carbon YP-50 as the active material, with a mass ratio of activated carbon YP-50, conductive carbon black, and binder polyvinylidene fluoride (PVDF) of 90:5:5). The rated capacity (nominal capacity) of the supercapacitor was designed to be 60F. The cell was immersed in electrolyte and sealed using an aluminum shell and adhesive granules. The activated carbon contains potassium (K), and the mass content of K in the active material layer is controlled by adjusting the K content in the activated carbon. In this embodiment, the mass content of K in the active material layer is 100 ppm. The compaction density of the active material layer is controlled by adjusting the coating amount and the calendering pressure. In this embodiment, the compaction density of the active material layer of the electrode plate is 0.8 g / cm³. 3 .

[0075] The electrolyte used N,N-dimethylpyrrolidone tetrafluoroborate (DMPBF4) as the electrolyte salt and acetonitrile (ACN) as the organic solvent. The content of DMPBF4 in the electrolyte was 20.5% and the content of acetonitrile was 79.5%. The conductivity of the electrolyte was tested at 25°C, and the test results are recorded in Table 1.

[0076] Examples 2-20 Examples 2-20 illustrate the supercapacitor and its preparation method disclosed in this invention, including most of the operational steps in Example 1, with the following differences: The contents of the compound shown in structural formula 1 (%), the contents of acetonitrile (%), the mass content of K element in the active material layer (ppm), and the conductivity of the electrolyte at 25°C are shown in Examples 2-20 of Table 1.

[0077] Comparative Examples 1-17 Comparative Examples 1-17 are used to compare and illustrate the supercapacitor and its preparation method disclosed in this invention, including most of the operational steps in Example 1, with the following differences: The contents of the compound shown in structural formula 1, a (%), other electrolyte salts and their mass contents, acetonitrile content, b (%), other solvents and their contents, mass contents of K element in the active material layer, u (ppm), and conductivity of the electrolyte at 25°C are shown in Comparative Examples 1 to 17 in Table 1.

[0078] Performance testing The supercapacitor prepared above was subjected to the following performance tests: (1) Pre-cycle (10 times): At 25°C, the supercapacitor is charged to the upper limit voltage of 3.0V at a constant current of 10mA / F(I) and left to stand for 15 seconds; then discharged to the voltage of 1.5V at a constant current of 10mA / F(I) and left to stand for 5 seconds. This cycle is repeated 10 times. The following data are recorded: The voltage after constant current charging to the upper limit voltage of 3.0V and resting for 15 seconds during the last cycle is U1; The time required for constant current discharge to reach 1.5V during the last cycle is t0, and the actual cutoff voltage is U2. During the last cycle, the voltage after constant current discharge to 1.5V and resting for 5 seconds is U3.

[0079] Calculate using the following formula: Initial capacity (F) at 25℃ = I×t0 / (U1-U2); The ESR of a capacitor at 25℃ is (U3-U2) / I.

[0080] (2) ESR test at -40℃: In a -40℃ low temperature chamber, the supercapacitor was charged to the upper limit voltage of 3.0V with a constant current of 10mA / F(I) and left to stand for 15 seconds; then discharged to the voltage of 1.5V with a constant current of 10mA / F(I) and left to stand for 5 seconds. This cycle was repeated 10 times, and the following data were recorded: The time required for constant current discharge to reach 1.5V during the last cycle is t1, and the actual cutoff voltage is U4. The voltage after constant current discharge to 1.5V and resting for 5 seconds during the last cycle is U5.

[0081] Calculate using the following formula: -40℃ capacitor ESR=(U5-U4) / I.

[0082] (3) 65℃ life test: In a 65℃ high-temperature chamber, the supercapacitor was charged at a constant current of 10mA / F(I) to the upper limit voltage of 3.0V, and then charged at a constant voltage of 3.0V for 1000h; the supercapacitor was then removed and cooled to 25℃, and then a charge-discharge test was performed under the same conditions as the pre-cycle test, 10 cycles were performed, and the following data were recorded: The voltage after constant current charging to the upper limit voltage of 3.0V and resting for 15 seconds during the last cycle is U6; The time required for constant current discharge to reach 1.5V during the last cycle is t2, and the actual cutoff voltage is U7.

[0083] Calculate using the following formula: The capacity (F) after float charging at 65℃ for 1000 hours is calculated as I×t² / (U6-U7). Capacity retention rate (%) after 1000 hours of float charging at 65℃ = Capacity after 1000 hours of float charging at 65℃ / Initial capacity at 25℃ × 100%.

[0084] The test results obtained from Examples 1-20 and Comparative Examples 1-17 are filled in Table 2. Table 2 The test results of Examples 1-20 and Comparative Examples 1-17 show that when carbon materials containing K in the active material layer are used as electrode plates, and the cyclic quaternary ammonium salt compound of structural formula 1 is added to the electrolyte as the electrolyte salt and acetonitrile as the main organic solvent, and the mass content of K in the active material layer (uppm), the content of electrolyte salt (a%), and the content of acetonitrile (b%) are controlled to meet the specific conditions of 0.1≤u*b / (100a)≤28, 13≤a≤49, 51≤b≤87, and 2≤u≤500, the prepared supercapacitor can effectively solve the technical problem that existing supercapacitors cannot simultaneously achieve low impedance and long cycle life, significantly reduce the equivalent series resistance of the supercapacitor, and greatly improve the cycle life and wide temperature range performance of the supercapacitor under high voltage conditions. It is speculated that in the supercapacitor system, the compound shown in Formula 1 has a smaller cation radius and higher structural rigidity, exhibiting significantly better oxidation stability and withstand voltage decomposition than the traditional quaternary ammonium salt system. This effectively reduces capacity decay caused by solute decomposition under high voltage, providing a foundation for long cycle life. Acetonitrile, as the main solvent, possesses low viscosity, high dielectric constant, and strong coordination ability, enabling efficient dissociation of the electrolyte salt and rapid ion transport, ensuring high ionic conductivity of the electrolyte. The pre-doped K element in the active material layer improves the electronic conductivity and ion transport performance of the electrode plate, reducing its impedance. Furthermore, it pre-constructs low-barrier ion transport channels for the electrolyte cations, alleviating adsorption / desorption resistance in carbon pores and further reducing the electrode plate-electrolyte interface impedance. Therefore, by adjusting the ratio of the three key parameters u, a, and b, a synergistic effect can be achieved, ultimately realizing the dual goals of reducing supercapacitor impedance and improving cycle life.

[0085] The test results of Comparative Examples 1-4 show that if the electrolyte salt content (a%), acetonitrile content (b%), and K element mass content (uppm) in the active material layer do not meet their respective defined ranges (13≤a≤49, 51≤b≤87, 2≤u≤500), even if the condition 0.1≤u*b / (100a)≤28 is met, the prepared supercapacitor still cannot simultaneously achieve low impedance and excellent cycle life. The test results of Comparative Examples 5-10 reveal that when the three parameters a, b, and u each meet their corresponding numerical ranges, but do not meet the core limiting condition 0.1≤u*b / (100a)≤28, the overall performance of the obtained supercapacitor still shows significant deterioration. This indicates a strong correlation and synergistic effect between the K element content, electrolyte salt content, and acetonitrile solvent content in the active material layer. Only when all three simultaneously meet the dual constraints of the numerical range and the core ratio formula, achieving a good balance, can the advantages of each component be fully utilized, achieving synergistic optimization of supercapacitor impedance reduction and cycle life.

[0086] The test results of Comparative Examples 11-17 show that the supercapacitor system provided by this invention uses the compound shown in Structural Formula 1 as the electrolyte salt and acetonitrile as the main organic solvent. If conventional quaternary ammonium salts such as tetraethylammonium tetrafluoroborate and 1,1-spirobispyrrolidineonium tetrafluoroborate are used to replace the compound shown in Structural Formula 1 as the electrolyte salt, or if other solvents such as propylene carbonate and sulfolane are used to replace acetonitrile as the main organic solvent, the overall performance of the prepared supercapacitor still deteriorates significantly, the equivalent series resistance increases significantly, the high-temperature cycling capacity retention rate decreases sharply, and the high-temperature float charge capacity retention rate decreases sharply.

[0087] Examples 21-25 Examples 21-25 illustrate the supercapacitor and its preparation method disclosed in this invention, including most of the operational steps in Example 1, with the following differences: The compounds represented by structural formula 1 were selected as shown in Examples 21-25 in Table 3.

[0088] Performance testing The supercapacitors prepared in the above embodiments were subjected to performance tests according to the performance test method of Example 1, and the test results were filled in Table 3.

[0089] Table 3 The test results from Examples 1 and 21-25 show that, in the supercapacitor system provided by this invention, under the conditions of 0.1≤ub / (100a)≤28, 13≤a≤49, 51≤b≤87, and 2≤u≤500, using compounds of structural formula 1 with different cation structures and different anion types as electrolyte salts all significantly improve the equivalent series resistance, high-temperature cycling capacity retention, and wide-temperature performance of the supercapacitor. The performance of each example is similar. This indicates that the technical solution of this invention has broad applicability to specific cation and anion types of compounds of different structural formula 1.

[0090] Examples 26-33 Examples 26-33 illustrate the supercapacitor and its preparation method disclosed in this invention, including most of the operational steps in Example 1, with the following differences: The compaction density of the active material layer is shown in Examples 26-33 in Table 4.

[0091] Performance testing The supercapacitors prepared in the above embodiments were subjected to performance tests according to the performance test method of Example 1, and the test results were filled in Table 4.

[0092] Table 4 The test results from Examples 1 and 26-33 show that, in the supercapacitor system provided by this invention, the compaction density of the active material layer is 0.5~1.0 g / cm³. 3 Within the specified range, both low equivalent series resistance and long cycle life of the supercapacitor can be achieved. The high-temperature float charge capacity retention rate is significantly better than that of samples with compaction densities exceeding this range, while the equivalent series resistance remains at a low level. This is because a suitable compaction density can balance the mechanical structural stability of the electrode plate with the diffusion efficiency of the electrolyte in the carbon pores, ensuring the effective exposure of the active sites of K element on the carbon material surface. This, combined with the K element doping electrode plate modification and the specific electrolyte system of this invention, forms a synergistic effect, thereby further improving the power characteristics and cycle stability of the supercapacitor.

[0093] Examples 34-40 Examples 34-40 illustrate the supercapacitor and its preparation method disclosed in this invention, including most of the operational steps in Example 1, with the following differences: The contents a (%) of the compound shown in structural formula 1, the contents and mass contents of other electrolyte salts, the contents b (%) of acetonitrile, the contents and mass contents of other solvents, and the conductivity of the electrolyte at 25°C are shown in Examples 34-40 of Table 5.

[0094] Table 5 Note: SBPBF4 is 1,1-spirobispyrrolidine onyx tetrafluoroborate. Performance testing The supercapacitors prepared in the above embodiments were subjected to performance tests according to the performance test method of Example 1, and the test results were filled in Table 6.

[0095] Table 6 The test results of Examples 1 and 34-40 show that in the supercapacitor system provided by the present invention, when the conductivity of the electrolyte at 25°C is in the preferred range of 30-65 mS / cm, the prepared supercapacitors can maintain excellent comprehensive performance, with lower equivalent series resistance, higher high-temperature float charge capacity retention rate, and lower impedance growth rate during cycling.

[0096] When the electrolyte conductivity is below 30 mS / cm, the resistance to ion migration in the electrolyte increases, the equivalent series resistance of the supercapacitor increases significantly, and the power characteristics deteriorate. When the electrolyte conductivity is above 65 mS / cm, the high electrolyte salt content leads to an increase in electrolyte viscosity, which in turn increases the resistance to ion transport in carbon pores. At the same time, high salt concentration will exacerbate side reactions, resulting in a significant decrease in the cycle life of the supercapacitor.

[0097] Meanwhile, the test results of Examples 34-40 also show that in the supercapacitor system provided by the present invention, the addition of other electrolyte salts or solvents has a certain degrading effect on the performance of the supercapacitor.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A supercapacitor, characterized in that, The device includes a diaphragm, an electrolyte, and two electrode plates. The diaphragm is located between the two electrode plates. Each electrode plate includes a current collector and an active material layer disposed on at least one surface of the current collector. The active material layer includes carbon material and potassium (K) element. The mass content of K element in the active material layer is u ppm based on the total mass of the active material layer. The electrolyte comprises an organic solvent and an electrolyte salt, wherein the organic solvent comprises acetonitrile, and the electrolyte salt comprises a compound shown in structural formula 1. Structural Formula 1 Among them, A - R1 and R2 are anions, each independently selected from C1 to C3 alkyl groups, and n is 0 or 1; Based on the total mass of the electrolyte, the content of the compound represented by structural formula 1 is a%, and the content of acetonitrile is b%. The supercapacitor satisfies the following conditions: 0.1≤u*b / (100a)≤28, and 13≤a≤49, 51≤b≤87, 2≤u≤500.

2. The supercapacitor according to claim 1, characterized in that, The supercapacitor satisfies at least one of the following conditions: (1)0.2≤u*b / (100a)≤12; (2)17.5≤a≤39.5; (3)60.5≤b≤82.5; (4)10≤u≤300。 3. The supercapacitor according to claim 1, characterized in that, The supercapacitor satisfies: 98≤a+b≤100.

4. The supercapacitor according to claim 1, characterized in that, The carbon material includes one or more of activated carbon, nano-carbon, graphene, lignin carbon, mesoporous carbon, carbon nanotubes, or porous carbon fibers.

5. The supercapacitor according to claim 1, characterized in that, The compaction density of the active material layer is 0.5~1.0 g / cm³. 3 .

6. The supercapacitor according to claim 1, characterized in that, The electrolyte has a conductivity of 30–65 mS / cm at 25°C.

7. The supercapacitor according to any one of claims 1 to 6, characterized in that, The anion A of the compound represented by structural formula 1 - Including one or more of tetrafluoroborate, hexafluorophosphate, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, bis(trifluoromethylsulfonyl)methyl, and perfluoroalkylsulfonate; and / or, The cation of the compound shown in structural formula 1 includes one or more of N,N-dimethylpyrrolidineonium, N,N-diethylpyrrolidineonium, N,N-dipropylpyrrolidineonium, N-methyl-N-ethylpyrrolidineonium, N-methyl-N-propylpyrrolidineonium, N-ethyl-N-propylpyrrolidineonium, N,N-dimethylpiperidineonium, N,N-diethylpiperidineonium, N,N-dipropylpiperidineonium, N-methyl-N-ethylpiperidineonium, N-methyl-N-propylpiperidineonium, and N-ethyl-N-propylpiperidineonium.

8. The supercapacitor according to claim 7, characterized in that, The anion A of the compound represented by structural formula 1 - It is tetrafluoroborate.

9. The supercapacitor according to any one of claims 1 to 6, characterized in that, The organic solvent is acetonitrile, and the compound represented by structural formula 1 is N,N-dimethylpyrrolidone tetrafluoroborate.

10. The supercapacitor according to any one of claims 1 to 6, characterized in that, The charging cutoff voltage of the supercapacitor is 2.7~3.2V; And / or, The supercapacitor operates in a temperature range of -40℃ to 65℃.